Mapping of tms8 gene for temperature-sensitive genic male sterility (TGMS) in rice (Oryza sativa L.) - Hussain, Appibhai J.; Ali, Jauhar; Siddiq, Ebrahimali A.; Gupta, Vidya S.; Reddy, Umesh K.; Ranjekar, Prabhakar K. (Plant Breeding, 2012)
Genetic analysis of F-2 and backcross populations of an induced temperature-sensitive genic male sterility (TGMS) mutant source F 61 with normal pollen parents revealed that TGMS trait was controlled by a single recessive gene. Molecular tagging of TGMS trait was attempted using polymorphic randomly amplified polymorphic DNA (RAPD) and simple sequence repeats (SSR) markers through bulked segregant analysis. The RAPD primers UBC 345830, UBC 313927, microsatellites RM224 and RM21 produced putative markers, which differentiate parents and bulks from sterile parent and sterile bulks. The RAPD analysis of individual F-2 plants with the primer UBC345(830) showed perfect marker-phenotype cosegregation. The 830-bp RAPD fragment, which segregated with TGMS locus at a distance of 1.33 cM, was eluted and cloned, and sequence information was used for designing sequence-characterized amplified region (SCAR) primer, which cosegregated with TGMS locus at a distance of 0.8 cM. TGMS locus was mapped onto chromosome 11 using RM21 and RM224, flanking it at a distance of 4.3 and 3.0 cM, respectively. The DNA markers tightly linked to TGMS gene (tms8) in F 61 can be cost effectively used for marker-assisted selection of TGMS trait.
Keywords: Bulked segregant analysis; randomly amplified polymorphic DNA; rice; sequence-characterized amplified region; SSR; temperature-sensitive genic male sterility